Relationship between microstructure and superconducting properties in hot-pressed Bi-2212/Ag ceramic composites. Issue 10 (December 2015) - Kahraman, F.; Sotelo, A.; Madre, M.A.; Diez, J.C.; Ozkurt, B.; Rasekh, Sh.
Abstract: Microstructure and superconducting properties of Bi2 Sr2 Ca1 Cu2 O8+ δ + x wt% Ag ( x =0 and 3) composite materials prepared by a sol–gel method and textured by a hot-pressing process have been investigated. Structural and microstructural studies have shown that Bi-2212/Ag composites exhibit better grain alignment, bigger grain sizes, and lower amount of secondary phases than the pure ones. These different microstructural features are reflected in the electrical properties which showed that room temperature resistivity and the transition width decrease when Ag is added, without modifying T c values. Moreover, magnetic properties have shown that Ag addition increases, in an important manner, the M – H loops surface, leading to higher J c values than the pure ones. This effect has been associated to the microstructural features which produce a decrease on the number of grain boundaries, together with a reinforcement of weak grain links with metallic Ag.